2022
DOI: 10.3390/molecules27082571
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Chitosan/Clay Composites for Safe and Effective Hemorrhage Control

Abstract: Uncontrolled hemorrhage from trauma or surgery can lead to death. In this study, chitosan/kaolin (CSK) and chitosan/montmorillonite (CSMMT) composites were prepared from chitosan (CS), kaolin (K), and montmorillonite (MMT) as raw materials to control bleeding. The physiochemical properties and surface morphology of CSK and CSMMT composites were analyzed by Fourier transform infrared spectrometry (FT-IR), X-ray diffraction (XRD), scanning electron microscopy (SEM), zeta potentials, and X-ray fluorescence (XRF).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…And the supernatant of corresponding RBC suspensions presented as colorless, which bore a resemblance to the PBS control group. The low hemolysis ratio of TPCI/MMT could be ascribed to the change of the surface charge and aggregation morphology for TPCI/MMT with the positively charged TCPI intercalated into MMT interlayers, which could affect its interaction with RBCs and relieve the hemolysis phenomenon . The morphology of RBCs in the TPCI/MMT group remained normal and intact, manifesting the good blood compatibility of TPCI/MMT.…”
Section: Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…And the supernatant of corresponding RBC suspensions presented as colorless, which bore a resemblance to the PBS control group. The low hemolysis ratio of TPCI/MMT could be ascribed to the change of the surface charge and aggregation morphology for TPCI/MMT with the positively charged TCPI intercalated into MMT interlayers, which could affect its interaction with RBCs and relieve the hemolysis phenomenon . The morphology of RBCs in the TPCI/MMT group remained normal and intact, manifesting the good blood compatibility of TPCI/MMT.…”
Section: Results and Discussionmentioning
confidence: 96%
“…The low hemolysis ratio of TPCI/MMT could be ascribed to the change of the surface charge and aggregation morphology for TPCI/MMT with the positively charged TCPI intercalated into MMT interlayers, which could affect its interaction with RBCs and relieve the hemolysis phenomenon. 58 The morphology of RBCs in the TPCI/MMT group remained normal and intact, manifesting the good blood compatibility of TPCI/MMT. In addition, TPCI also exhibited unobvious hemolytic toxicity (2.2%) under the same concentration.…”
Section: Evaluation Of Antibacterial Activity In Vitromentioning
confidence: 86%
“…121,122 It has also been found that the negative charge of kaolin causes activation of XI, prekallikrien, and cofactor HWK-kininogen and MMT can activate Factors VI and VII. 121,123 Both kaolin and MMT can also contribute to physical hemostasis through the absorption of blood.…”
Section: Minerals and Other Naturally Occurring Hemostatic Agentsmentioning
confidence: 99%
“…Montmorillonite (Mt), as a natural 2D nanolayered aluminomagnesium silicate clay, has been widely used throughout history as bioactive agents in diarrhea, dysentery, and other intestinal ailments. Nowadays, Mt is not only approved by the Food and Drug Administration (FDA) as an additive for pharmaceutical products but also popular in industry for manufacturing commercial products because it is biocompatible and easily available at a low price. Mt is a three-layered lamellar structure with aluminum oxide octahedral sheet in the middle and two silicon oxygen tetrahedral sheets on the top and bottom sides. , Such a highly ordered packing structure endows Mt excellent adsorption, expansibility, and cation exchange characteristics. , It has been reported that Mt has excellent water-absorbent expansive properties, which can activate coagulation factors at the bleeding site, promote vasoconstriction, and slow down local blood flow so as to achieve the purpose of rapid hemostasis. , Moreover, Mt can adsorb bacteria and bacterial enterotoxins which indicates certain antibacterial activity. , …”
Section: Introductionmentioning
confidence: 99%
“…The wound-healing process proceeds in four phases: hemostasis, inflammation, proliferation, and remodeling . Among these, uncontrollable bleeding and bacterial infection are the main challenges in the early stages of wound healing. , To stop bleeding quickly and prevent infection, wounds are often treated clinically with hemostatic materials and antibiotic drugs. , Currently, there are many clinically available hemostatic materials, such as conventional wound dressing, , microporous aluminosilicates (zeolites and clays), , or various polymer-based materials (e.g., hydrogels, sponges, and films). Although all of them have hemostatic functions, they still have some disadvantages. For example, conventional wound dressings are usually less effective and need long-term treatment .…”
Section: Introductionmentioning
confidence: 99%